Structure and Physical Properties of Cardamonin: A Spectroscopic and Computational Approach - Iwona Budziak; Marta Arczewska; Daniel M. Kamiński (Molecules, 2020)
This is the first study of the crystal structure of cardamonin (CA) confirmed using single-crystal XRD analysis. In the crystal lattice of CA, two symmetry independent molecules are linked by hydrogen bonds within the layers and by the π···π stacking interactions in the columns which lead to the occurrence of two types of conformations among the CA molecules in the crystal structure. To better understand the stability of these arrangements in both crystals and the gaseous phase, seven different CA dimers were theoretically calculated. The molecular structures were optimized using density functional theory (DFT) at the B3LYP/6–311G+(d,p) level and the spectroscopic results were compared. It was found that the calculated configurations of dimer I and III were almost identical to the ones found in the CA crystal lattice. The calculated UV-Vis spectra for the CA monomer and dimer I were perfectly consistent with the experimental spectroscopic data. Furthermore, enhanced emissions induced by aggregated CA molecules were registered in the aqueous solution with the increase of water fractions. The obtained results will help to further understand the relation between a variety of conformations and the biological properties of CA, and the results are also promising in terms of the applicability of CA as a bioimaging probe to monitor biological processes.